A Case of Concomitant Perforated Acute Cholecystitis and Pancreatitis - Marlon Perera; Toan Pham; Sumeet Toshniwal; Yasmin Lennie; Steven Chan; Nezor Houli (Case Reports in Surgery)
Introduction. Concomitant cholecystitis and gallstone pancreatitis is an infrequent clinical encounter, reported sparsely in the literature. Concurrent acute cholecystitis and pancreatitis complicated by gall bladder perforation has not been reported before. Presentation of Case. We report a 39-year-old female presenting with concomitant cholecystitis and acute pancreatitis, complicated by gallbladder perforation. Discussion. There is much controversy surrounding the timing of cholecystectomy following gallstone pancreatitis, with the recent literature suggesting that “early” operation is safe. In the current case, gallbladder perforation altered the “routine” management of gallstone pancreatitis and posed as a management dilemma. Conclusion. Clinical judgement dictated timing of operative management and ultimately cholecystectomy was performed safely.